Impairment of Glucose Uptake Induced by Elevated Intracellular Ca2+ in Hippocampal Neurons of Malignant Hyperthermia-Susceptible Mice - Arkady Uryash; Alfredo Mijares; Jose A. Adams; Jose R. Lopez (Cells)
Malignant hyperthermia (MH) is a genetic disorder triggered by depolarizing muscle relaxants or halogenated inhalational anesthetics in genetically predisposed individuals who have a chronic elevated intracellular Ca2+ concentration ([Ca2+]i) in their muscle cells. We have reported that the muscle dysregulation of [Ca2+]i impairs glucose uptake, leading to the development of insulin resistance in two rodent experimental models. In this study, we simultaneously measured the [Ca2+]i and glucose uptake in single enzymatically isolated hippocampal pyramidal neurons from wild-type (WT) and MH-R163C mice. The [Ca2+]i was recorded using a Ca2+-selective microelectrode, and the glucose uptake was assessed utilizing the fluorescent glucose analog 2-NBDG. The MH-R163C hippocampal neurons exhibited elevated [Ca2+]i and impaired insulin-dependent glucose uptake compared with the WT neurons. Additionally, exposure to isoflurane exacerbated these deficiencies in the MH-R163C neurons, while the WT neurons remained unaffected. Lowering [Ca2+]i using a Ca2+-free solution, SAR7334, or dantrolene increased the glucose uptake in the MH-R163C neurons without significantly affecting the WT neurons. However, further reduction of the [Ca2+]i below the physiological level using BAPTA decreased the insulin-dependent glucose uptake in both genotypes. Furthermore, the homogenates of the MH-R163C hippocampal neurons showed an altered protein expression of the PI3K/Akt signaling pathway and GLUT4 compared with the WT mice. Our study demonstrated that the chronic elevation of [Ca2+]i was sufficient to compromise the insulin-dependent glucose uptake in the MH-R163C hippocampal neurons. Moreover, reducing the [Ca2+]i within a specific range (100–130 nM) could reverse insulin resistance, a hallmark of type 2 diabetes mellitus (T2D).